Turkish Translation, Accreditation, and Validation of the Otitis Media-6 Questionnaire - Yazıcı, Alper (European Journal of Therapeutics, 2023)
Objective: Otitis media is one of the most common ear disorders occurring in childhood, which causes alterations in communication between parents and children, thereby having a significant effect on the health-related quality of life. Otitis Media-6 questionnaire (OM-6) is a Likert-type scale used to assess the health-related quality of life in children with otitis media. In this study, our aim was to create a consistent, reliable, and valid Turkish version of the OM-6. Methods: Children with otitis media presenting with effusion and healthy children were enrolled in this study between February 2019 and September 2019. The OM-6 test was administered to three different groups, including preoperative, postoperative, and control, among the children who had undergone ventilation tube insertion operation and among the healthy children. Results: The overall scores of children with otitis media presenting with effusion exhibited a changing pattern, indicating a statistical significance in the evaluation of the health-related quality of life. The Turkish version of OM-6 includes the scores of construct validity (Spearman values between 0, 58-0, 89), internal consistency (Cronbach’s alpha values between 0, 88-0, 96), and reliability (Pearson correlation value between 0, 67-0, 91). These scores exhibited a statistical significance. Conclusion: The Turkish version of OM-6 is a stable, valid questionnaire with internal consistency